What Drives ECB Monetary Policy? - Clemens J. M. Kool (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2005)
In this paper I have analyzed ECB interest rate setting in the first 5 years of its existence. Contrary to popular belief and continuous ECB statements, the ECB has not acted has as an obsessed inflation fighter. By any measure, output considerations do play a significant role in the ECB's policy rule. If anything, the ECB has been on the loose side, especially since 2001, when taking economic development in the euro area as a whole as the starting point. Actual interest rates have been consistent with German (and to a lesser extent French) preferences, however. It suggests the ECB puts a dominant weight on German economic developments. Small peripheral countries receive too low weight rather than too high. In case the ECB actually focuses on euro area wide developments, its looseness is comparable to that of the Fed. In case ECB policy actually is geared towards Germany's preferences – or perhaps the average German-French preferences – the ECB has been much closer to a standard Taylor-rule interest rate setting than the Fed. In that scenario, the Fed indeed has been much more aggressive in the lowering of its interest rates in the face of adverse economic shocks.
Keywords: 330